Problematika Pendidikan Islam dalam Menyiapkan Sumber Daya Manusia untuk Dunia Kerja di Era Globalisasi (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The era of globalization demands that education systems produce human resources who are skilled, adaptable, and capable of competing in the international job market. However, several issues arise in efforts to prepare graduates who are well aligned with industry requirements. These challenges include the mismatch between competencies taught in educational institutions and those required by the workforce, limited digital literacy and technological mastery, the lack of soft skills development, and insufficient collaboration between schools and industries. Rapid technological advancements often result in curricula that lag behind the current skill demands of the labor market. Moreover, many students still lack the mindset, creativity, and adaptability needed to face global competition. This literature-based study aims to identify the main educational problems in preparing human resources for the world of work and propose strategic directions for improvement. Findings highlight the necessity of competency-based curriculum transformation, enhanced vocational training, integration of technology-based learning, and stronger partnerships between education providers and industry sectors. Enhancing teacher quality is also crucial to ensure learning processes remain relevant to global demands. By optimizing the roles of all stakeholders, education can produce graduates who possess not only technical expertise but also essential 21st-century skills such as communication, collaboration, problem-solving, and leadership. Therefore, education becomes the primary foundation for preparing a generation capable of competing globally and contributing to national development.